Driver responses to navigation information on full–windshield, head–up displays. (4th August 2014) - Steinfeld, A.; Green, P.
While seated in a vehicle mockup, drivers (6 young, 6 old) made same/different judgements of simultaneously shown pairs of slides (real intersections and navigation displays that could be for them). The navigation information was presented on either an instrument panel (IP) display or superimposed on the road scene, simulating a full–windshield, head–up display (HUD). Response times to full–windshield HUDs (1170 ms) were shorter than IP displays (1511 ms), a difference of about 20%. HUD colour had no significant effect on response time, but displays aligned with the road scene produced times slightly faster than misaligned ones (34 ms difference). As reported previously, plan and aerial views were responded to faster than perspective views. Due to high error rates in some conditions, continued experimental evaluation of full–windshield HUDs is desired.